A Comparative Analysis of the Metabolomic Response of Electron Beam Inactivated E. coli O26:H11 and Salmonella Typhimurium ATCC 13311 - Bhatia, Sohini S.; Pillai, Suresh D. (Frontiers in Microbiology, 2019)
Ionizing radiation such as electron beam (EB) and gamma irradiation inactivate microbial cells preventing their multiplication. These cells, however, are structurally intact and appear to have residual metabolic activity. We were interested in understanding the metabolic pathways that were still functional in EB-inactivated cells. Therefore, the primary objective of this study was to compare the metabolites accumulating in EB-inactivated pathogens E.coli 026:H11 and S. Typhimurium immediately after EB inactivation and 24 hours post-inactivation. Defined aliquots (109 CFU/mL) of E.coli O26-H11 (TW 1597) and S. Typhimurium (ATCC 13311) suspended in phosphate-buffered saline were exposed to lethal EB doses of 3 kGy and 2 kGy respectively. Complete inactivation (inability of cells to multiply) was confirmed by traditional plating methods. An untargeted analysis of the primary metabolites accumulating in un-irradiated (control) cells, EB-inactivated cells immediately after irradiation, and EB-inactivated cells that were incubated at room temperature for 24 h post EB inactivation was performed using gas chromatography/mass spectrometry. A total of 349 different metabolites were detected in the EB-inactivated S. Typhimurium and E.coli O26:H11 cells, out of which, only 50% were identifiable. In S. Typhimurium, 98 metabolites were expressed at statistically different concentrations (P < 0.05) between the 3 treatment groups. In E. coli O26:H11, 63 metabolites were expressed at statistically different concentrations (P < 0.05) between the 3 treatment groups. In both these pathogens, the β -alanine, alanine, aspartate, and glutamate metabolic pathways were significantly impacted (P < 0.01). Furthermore, the metabolomic changes in EB-inactivated cells were amplified significantly after 24 hour storage at room temperature in phosphate-buffered saline. These results suggest that EB-inactivated cells are very metabolically active and, therefore, the term Metabolically Active yet Non-culturable is an apt term describing EB-inactivated bacterial cells.